Διαφωτισμός και επανάσταση: Η διαπλοκή δύο όρων στα ιστορικά τους συμφραζόμενα - Kitromilides, Paschalis M. (The Gleaner, 2024)
Enlightenment and Revolution. The interconnection of two historiographical terms in their multiple contexts This brief essay attempts to address in an exploratory way a challenging question concerning the interconnection of two controversial historiographical terms, Enlightenment and Revolution. The term Enlightenment is defined on the basis of Immanuel Kant’s classic discussion in his 1784 essay and the multiple uses and understandings of the term and idea of Enlightenment are followed through their subsequent transformations in the milestones of relevant historiography. The term Revolution and its changing meanings are also traced in the sources from Herodotus and Thucydides to the discussion of the «Age of Revolution». The unending controversies over the possible causal interconnection of the broad phenomena denoted by the two terms are acknowledged, but it is suggested that the whole issue might be more effectively clarified if considered in specific historical contexts, by reference to which questions of evidence and historiographical interpretation might be more practically controlled and appraised. It is further suggested that the consideration of the relevant issues in the historical context of Southeastern Europe offers a realistic possibility for an informed judgement on the broader theoretical question on the basis of the evidence of the concrete historical experience of the region. This kind of contextualization in turn may provide correctives to the occasional excesses of theoretical debates.